Exploring Conflicts Between Work and Care: Vulnerable Populations and Paid Family Leave. Issue 3 (July 2020) - Gates, Alice B.; Pacheco, Dorian; Mejía, Anaceli; Varquez, Caitlin; Martínez, Emma; Dillard, Danielle
This exploratory study aims to increase understanding of conflict related to integrating work and care among racial and ethnic minority and economically disadvantaged populations. Employing community-based research methods, we conducted qualitative interviews with women about their caregiving needs following the birth of a child. Interviewees struggled to balance their families' need for care with income and other basic needs, and they reported experiencing physical, emotional, and financial strain. The process of negotiating leave created additional stress for workers and families. Our analysis suggests that the conflict between work and care is associated with increased social risk and vulnerability for members of already vulnerable and marginalized groups. Drawing on these insights, specific implications for paid family leave policy are discussed.